2018
DOI: 10.1021/acs.jpcc.8b01187
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Study of Co-Doped Magnetosome Chains

Abstract: Magnetotactic bacteria synthesize a chain of magnetic nanoparticles, called magnetosome chain, used to align and swim along the geomagnetic field lines. In particular, Magnetospirillum gryphiswaldense biomineralize magnetite, Fe3O4. Growing this species in a Co-supplemented medium, Co-doped magnetite is obtained, tailoring in this way the magnetic properties of the magnetosome chain. Combining structural and magnetic techniques such as transmission electron microscopy, energy-dispersive x-ray spectroscopy, X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 56 publications
10
39
0
Order By: Relevance
“…Note that, according to EDS (see the supplementary information), the Co content in the magnetosomes is only 1.6% at./Fe, thus the Co ferrite in the magnetosomes is not stoichiometric ( Co 0.05 Fe 2.95 O 4 ). In spite of the low Co content, it has been previously reported that the magnetic properties of Co-magnetosomes change notably with respect to the undoped ones [20][21][22] .…”
Section: Resultsmentioning
confidence: 97%
“…Note that, according to EDS (see the supplementary information), the Co content in the magnetosomes is only 1.6% at./Fe, thus the Co ferrite in the magnetosomes is not stoichiometric ( Co 0.05 Fe 2.95 O 4 ). In spite of the low Co content, it has been previously reported that the magnetic properties of Co-magnetosomes change notably with respect to the undoped ones [20][21][22] .…”
Section: Resultsmentioning
confidence: 97%
“…It should be noted that, such form of thermal dependence (as M 2 ) cannot be extrapolated to lower temperatures in our case, due to the presence of the Verwey phase transition at around 100 K. A detailed analysis of this issue requires the collection of additional data as a function of temperature and a more complex modeling to take account for the thermal dependence of the magnetocrystalline contribution to the anisotropy that is out of the scope of this work. This type of study have been already done in the literature, either with magnetosome [64], whose thermal behavior is expected to be similar to the samples presented in this work, or very recently with Mn-Zn ferrites [65]. The overall agreement between experiments and simulations in both SAR evolution ( Figure 10) as well as in AC hysteresis loops (see Supporting Information Figure S13) is quite surprising since simplifications made in the modeling are really strong: size distribution has been not taken into account and, most importantly, magnetic dipolar interactions have not been explicitly considered.…”
Section: The Specific Absorption Rate As a Function Of Field And Freqmentioning
confidence: 99%
“…Laboratory synthesized nanoparticles require encapsulation in biopolymers to be biocompatible and to remain stable in suspension inside the body over long periods of time. Already biocompatible alternatives are natural or engineered biosynthesized magnetite nanoparticles from bacteria ( Hergt et al, 2005 ; Fantechi et al, 2014 ; Elfick et al, 2017 ; Marcano et al, 2018 ). Genetically controlled in situ syntheses of nanoparticles in neurons could in the future completely remove the need for particle delivery but so far has failed to produce particles showing clear heating ( Wesolowski et al, 2009 ; Pollithy et al, 2011 ; Stanley et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%